Haplotype determination of the upstream regulatory region and the second exon of the BoLA-DRB3 gene in Holstein cattle - Goszczynski, Daniel Estanislao (2014)
Polymorphisms of the BoLA-DRB3 gene are located primarily in the second exon [antigen binding site (ABS)] and, to a lesser extent, in the upstream regulatory region (URR). It can be hypothesised that exon 2 and the URR are under different types of natural selection. The aim of this work was to determine the URR-exon 2 haplotypes; 34 Holstein samples were genotyped by direct sequencing. A total of 7 URR alleles and 23 exon 2 alleles were detected, and 3 of the URR alleles were novel. Our results may suggest that no relationship exists between the URR and exon 2 of the BoLA-DRB3 gene (linkage disequilibrium P value > 0.05), most likely due to recombination over time. Our results also suggest that both regions of class II genes may be included in the development of new genotyping methods based on nextgeneration DNA sequencing technologies.